2020
DOI: 10.1093/ibd/izz282
|View full text |Cite
|
Sign up to set email alerts
|

Early Surgery Versus Biologic Therapy in Limited Nonstricturing Ileocecal Crohn’s Disease—A Decision-making Analysis

Abstract: Background Surgery is the preferred option for patients with symptomatic localized fibrostenotic ileocecal Crohn’s disease (CD) but not for those with predominantly active inflammation without obstruction. The benefit of early surgery in patients with a limited nonstricturing ileocecal CD over biologic treatment is still a debate. Objective Our objective is to formulate a decision analysis model based on recently published da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A review conducted by Broide et al . [ 41 ] has also suggested that starting early biologics is more cost-effective when compared to surgery and conventional therapy among adults. Similar studies among children are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A review conducted by Broide et al . [ 41 ] has also suggested that starting early biologics is more cost-effective when compared to surgery and conventional therapy among adults. Similar studies among children are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Some even question whether the role of medical therapy is to delay the eventuality of surgery (25,27). Several recent studies suggest surgical excision to provide a better quality of life and a significant reduction in cost compared to anti-TNF therapy in isolated ileocolic disease (25,29).…”
Section: Stricturoplasty Vs Small Bowel Resectionmentioning
confidence: 99%
“…And long-term studies have shown that after resection, 50% of patients will never require reoperation. 11 Some evidence suggests that postoperative IFX treatment may lead to a lower recurrence rate (9.1%-24% within 1 year) compared with not using IFX postoperatively (81%-85% within 1 year). [12][13][14][15][16] However, several studies have shown that preoperative use of IFX can lead to an increased risk of postoperative complications such as sepsis, abdominal abscess and anastomotic leakage.…”
Section: Introductionmentioning
confidence: 99%